Altered lateralization of the cingulum in deployment‐related traumatic brain injury: An ENIGMA military‐relevant brain injury study. Issue 5 (30th December 2022) - Dennis, Emily L.; Newsome, Mary R.; Lindsey, Hannah M.; Adamson, Maheen; Austin, Tara A.; Disner, Seth G.; Eapen, Blessen C.; Esopenko, Carrie; Franz, Carol E.; Geuze, Elbert; Haswell, Courtney; Hinds, Sidney R.; et al.
Abstract: Traumatic brain injury (TBI) in military populations can cause disruptions in brain structure and function, along with cognitive and psychological dysfunction. Diffusion magnetic resonance imaging (dMRI) can detect alterations in white matter (WM) microstructure, but few studies have examined brain asymmetry. Examining asymmetry in large samples may increase sensitivity to detect heterogeneous areas of WM alteration in mild TBI. Through the Enhancing Neuroimaging Genetics Through Meta‐Analysis Military‐Relevant Brain Injury working group, we conducted a mega‐analysis of neuroimaging and clinical data from 16 cohorts of Active Duty Service Members and Veterans ( n =  2598). dMRI data were processed together along with harmonized demographic, injury, psychiatric, and cognitive measures. Fractional anisotropy in the cingulum showed greater asymmetry in individuals with deployment‐related TBI, driven by greater left lateralization in TBI. Results remained significant after accounting for potentially confounding variables including posttraumatic stress disorder, depression, and handedness, and were driven primarily by individuals whose worst TBI occurred before age 40. Alterations in the cingulum were also associated with slower processing speed and poorer set shifting. The results indicate an enhancement of the natural left laterality of the cingulum, possibly due to vulnerability of the nondominant hemisphere or compensatory mechanisms in the dominant hemisphere. The cingulum is one of the last WM tracts to mature, reaching peak FA around 42 years old. This effect was primarily detected in individuals whose worst injury occurred before age 40, suggesting that the protracted development of the cingulum may lead to increased vulnerability to insults, such as TBI. Abstract : Through collaborative mega‐analysis, we examined alterations in white matter asymmetry in deployment‐related traumatic brain injury in a sample of nearly 2600. We found greater asymmetry of the cingulum bundle that was not accounted for by other confounding variables. Cingulum microstructural organization was also associated with cognitive function.